Levels, Patterns and Distribution of Consumption Expenditure of Farmers and Agricultural Labourers in Rural Punjab. (September 2019) - Singh, Gian; Anupama,; Kaur, Gurinder; Kaur, Rupinder; Kaur, Sukhvir
The objective of the present paper is to analyse levels, patterns and distribution of consumption expenditure by farmers and agricultural labourers in rural Punjab. An attempt has also been made to analyse the same trends across social groups and observe how caste interacts with resource ownership and leads to unequal outcomes. The study reveals a positive relationship between farm size and consumption levels, and also shows that caste-based discrimination becomes overt at higher levels of living. The farming communities may show a level of equality in deprivation but not in achievements. We see that most poor farmers and agricultural labourers spend on basic needs, thus leaving lesser amounts to be spent on durables and services. Things worsen for socially marginalised groups. The majority of households belonging to these categories have an average propensity to consume greater amounts which forces them to borrow money to make both ends meet. Finally, this study offers some policy suggestions to save such communities from a vicious debt trap and help them improve their living standards.